2018
DOI: 10.1016/j.bjm.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Histophilus somni -associated syndromes in sheep from Southern Brazil

Abstract: Histophilus somni is a Gram-negative bacterium that is associated with a disease complex (termed histophilosis) that can produce several clinical syndromes predominantly in cattle, but also in sheep. Histophilosis is well described in North America, Canada, and in some European countries. In Brazil, histophilosis has been described in cattle with respiratory, reproductive, and systemic disease, with only one case described in sheep. This report describes the occurrence of Histophilus somni-associated disease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Collectively, fetal infection by these pathogens was probably due to intrauterine infection resulting from transplacental transmission [40,41]. Consequently, most of the disease agents herein identified may be classified either as primary or secondary fetopathic agents of cattle [24,40] and could have produced direct or indirect effects on fetal survival [41]. The primary fetopathy agents herein identified (BVDV, BoAHV1, N. caninum, B. abortus, and Leptospira spp.)…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Collectively, fetal infection by these pathogens was probably due to intrauterine infection resulting from transplacental transmission [40,41]. Consequently, most of the disease agents herein identified may be classified either as primary or secondary fetopathic agents of cattle [24,40] and could have produced direct or indirect effects on fetal survival [41]. The primary fetopathy agents herein identified (BVDV, BoAHV1, N. caninum, B. abortus, and Leptospira spp.)…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, some well-known pathogens of reproductive disease in cattle, such as BVDV, BoAHV1, Leptospira spp., B. abortus, and M. bovis, were also identified and associated with pulmonary alteration(s), collaborating with the results of previous studies that have demonstrated B. abortus [19,20], M. bovis [17], BoAHV1 [16,21], BVDV [10] in the fetal lungs of cattle. Collectively, fetal infection by these pathogens was probably due to intrauterine infection resulting from transplacental transmission [40,41]. Consequently, most of the disease agents herein identified may be classified either as primary or secondary fetopathic agents of cattle [24,40] and could have produced direct or indirect effects on fetal survival [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sheep strain of H. somni can infect cattle and goats, while the cattle strain cannot infect sheep 3. [19][20][21]…”
Section: Bacterial Pneumoniamentioning
confidence: 99%
“…H somni ‐associated disease is more commonly reported in cattle but cases of meningoencephalitis, bronchopneumonia, septicaemia and myocarditis have been recorded in sheep 1 …”
Section: Small Ruminantsmentioning
confidence: 99%